Sieciowy aktywizm. Oddolne działania w odpowiedzi na konsekwencje dynamicznego rozprzestrzeniania się informacji oraz medialności kryzysów światowych - Kwiatkowska, Zuzanna; Strzelecka, Maria (Humaniora. Czasopismo Internetowe, 2024)
This article aims to characterize grassroots activities in an era of increasingly rapid spread of information and mediatization of conflicts and global disasters. In the current environment, dubbed dense mediaenvironment by Eyal Weizman, new opportunities are being created to build forms of public engagement. Their development is particularly influenced by such phenomena as OSINT, aspects of which are described in the article. The grassroots activities described detail the research methodologies used, based on data and open sources. The contexts of Fortress Europe are also presented, and an analysis is made of the circumstances that resulted in the humanitarian crisis on the Polish-Belarusian border. The following part of the article describes the background of the creation and operation of the wallobserver.eu online platform. It focuses on the problem of archiving media articles leading the narrative around migration situations happening on the external land borders of the European Union and the process of its fortification.